Exploring the Neural Basis of Stereotyped, Automatized, and Habitual Behaviours: Common Mechanisms or Distinct Motor Skills? - Florio, Tiziana M. (Recent Updates in Disease and Health Research Vol. 6, 2024)
This review focuses on the basic classification of higher motor control functioning, considering recent advances in the structural knowledge of the basal ganglia and computational model of basal ganglia functioning. We discuss the capability of the basal ganglia in executing ordered motor patterns in which any single movement is linked to each other into an action, and many actions are ordered into each other, giving them a syntactic value to the final behaviour. In recent decades, a thorough understanding of the higher executive processes of motor control has been created. Diverse technology strategies have been used to address important objectives. Our ability to respond to better answers that have been proposed and to examine complex neurological system functioning more thoroughly than before has significantly enhanced due to an abundance of fresh data. Behaviour is the observable result of the invisible, as complex cerebral functioning. Many pathological states are observed after the symptomatology categorization of behavioural impairments is achieved. Motor, non-motor and psychiatric signs are greatly contributed by many neurological/psychiatric disorders. Along with the cerebral cortex, the basal ganglia contribute to the expression of behaviour by promoting the correct action schemas and the selection of appropriate subgoals based on the evaluation of action outcomes. Stereotypic, automatized, and habitual behaviour constructs and controls are the expression of successive stages of rule internalization and categorization aimed at producing the perfect spatial-temporal control of motor command. With the release of numerous wearable devices and the influx of new data, there will be an unprecedented level of movements categorization. As this goal is achieved, the remarkable cerebral capacity to generate skills in an emergent manner would become accessible.